2004
DOI: 10.1111/j.1474-9728.2004.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial hTERT exacerbates free‐radical‐mediated mtDNA damage

Abstract: SummaryTelomerase is often re-activated in human cancers and is widely used to immortalize cells in culture. In addition to the maintenance of telomeres, telomerase has been implicated in cell proliferation, genomic instability and apoptosis. Here we show that human telomerase reverse transcriptase (hTERT) is targeted to the mitochondria by an N-terminal leader sequence, and that mitochondrial extracts contain telomerase activity. In seven different human cell lines, mitochondrial telomerase increases hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
265
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(288 citation statements)
references
References 54 publications
(70 reference statements)
18
265
2
3
Order By: Relevance
“…Although our results do not clearly identify the source of increased steady-state levels of superoxide in the DC cells, our findings showing MitoSOX oxidation being altered, coupled with the differential effects seen with manipulations of O 2 tension, support the hypothesis that mitochondria may represent a significant source of superoxide in DC cells containing dysfunctional telomerase and telomeres. This is of interest because recent studies have implicated TERT in localizing to the mitochondria and modulating ROS (1,42,43). However, our studies showing that a TERT mutant without a mitochondria localization signal was still able to reduce steady-state levels of superoxide in DC cells do not support this model.…”
Section: Discussioncontrasting
confidence: 56%
“…Although our results do not clearly identify the source of increased steady-state levels of superoxide in the DC cells, our findings showing MitoSOX oxidation being altered, coupled with the differential effects seen with manipulations of O 2 tension, support the hypothesis that mitochondria may represent a significant source of superoxide in DC cells containing dysfunctional telomerase and telomeres. This is of interest because recent studies have implicated TERT in localizing to the mitochondria and modulating ROS (1,42,43). However, our studies showing that a TERT mutant without a mitochondria localization signal was still able to reduce steady-state levels of superoxide in DC cells do not support this model.…”
Section: Discussioncontrasting
confidence: 56%
“…The immortalized human mammary epithelial cell line hTERT184 was derived from the normal human mammary epithelial 184 cell line (18,19) and was a kind gift from J. Carl Barrett (National Cancer Institute, Bethesda, MD). Cells were grown in defined MEGM media (Cambrex) supplemented with 5 Ag/mL transferrin (Sigma), 10 À5 mol/L isoproterenol (Sigma), and 250 Ag/mL geneticin (Invitrogen) in a humidified 2% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…However, due to the lack of highly specific antibodies against hTERT and low expression of endogenous hTERT in cells, it has not been examined whether endogenous hTERT localizes in mitochondria under physiological condition. Further analysis shows that the mitochondrial telomerase sensitizes the damage effects of H 2 O 2 on mtDNA, presumably via modulation of metal homeostasis [28]. In addition, studies indicate that mitochondrial localization of telomerase functions is a determinant of hydrogen peroxide-induced mitochondrial DNA damage and apoptosis [29].…”
Section: Telomerase In Apoptosismentioning
confidence: 99%
“…It has been shown that the catalytic subunit of telomerase hTERT contains a mitochondrial localization signal peptides at its N-terminal 20 amino acids which targets hTERT to mitochondria, resulting in active telomerase in this organelle [28]. These experiments were done by transiently over-expression of In all case tested, a mitochondrial localization of GFP-hTERT was observed by confocal microscopy and by the telomeric repeat amplification protocol (TRAP).…”
Section: Telomerase In Apoptosismentioning
confidence: 99%